Financial and current account interrelationship, an ARDL bounds test approach: the case of Tunisia before the Jasmine Revolution. (4th February 2020) - Farhoud, Hager; Taleb, Lotfi
The present paper investigates the long and short-run dynamics between the surplus of aggregated and disaggregated financial account and the persistent pattern of current account deficit in Tunisia during the whole period before the Jasmine Revolution (1977 to 2011). The results highlight evidence of long-run cointegration relationships between current account and both financial account and its components in the Tunisian context, indicating that the current account deficit reflects the surplus of financial account. With regard to the causality tests, the results found suggest also long and short-run bidirectional links between current account and both financial account, foreign direct investment, and external borrowing, and between foreign direct investment and debt. The findings prove also, that there is evidence of unidirectional causality from portfolio investment to current account over the long-run and from, foreign direct investment and debt to portfolio investment, over the short-run.